2019
DOI: 10.1155/2019/6104574
|View full text |Cite|
|
Sign up to set email alerts
|

Detarium microcarpum, Guiera senegalensis, and Cassia siameaInduce Apoptosis and Cell Cycle Arrest and Inhibit Metastasis on MCF7 Breast Cancer Cells

Abstract: Despite the availability of anticancer drugs, breast cancer remains the most death-causing tumor-related disease in women. Hence, there is a need for discovery and development of efficient alternative drugs, and sources such as plants need to be explored. In this study, antioxidant capacities and inhibitory effects against MCF7 cells of the extracts of stem bark of three Nigerian medicinal plants (Detarium microcarpum, Guiera senegalensis, and Cassia siamea) were investigated. The D. microcarpum extracts had t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 40 publications
1
16
1
1
Order By: Relevance
“…One milligram of the synthesized nanoparticles quenched 53.73% of the oxidant DPPH solution, and its TEAC value was calculated to be 300.91 ± 13.42 μ M Trolox/mg silver nanoparticles. The amount is considered significant when compared with the antioxidant capacities of other nanoparticles and medicinal plants [ 21 , 35 37 ]. El-Rafie and Hamed [ 38 ] reported that Terminalia catappa extract-mediated silver nanoparticles had significant free radical scavenging effect and high antioxidant activity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One milligram of the synthesized nanoparticles quenched 53.73% of the oxidant DPPH solution, and its TEAC value was calculated to be 300.91 ± 13.42 μ M Trolox/mg silver nanoparticles. The amount is considered significant when compared with the antioxidant capacities of other nanoparticles and medicinal plants [ 21 , 35 37 ]. El-Rafie and Hamed [ 38 ] reported that Terminalia catappa extract-mediated silver nanoparticles had significant free radical scavenging effect and high antioxidant activity.…”
Section: Resultsmentioning
confidence: 99%
“…The DPPH assay was carried out using a modification of the procedure described by [ 21 ]. Briefly, 150 μ l of 0.2 mM DPPH solution (Sigma-Aldrich, Darmstadt, Germany) was added to either 50 μ l of the synthesized silver nanoparticles or 50 μ l of varying concentrations (0, 30, 60, 120, 240, and 480 μ g/ml) of Trolox antioxidant solution (Acros Organics, Newton Dr, Carlsbad, CA, USA) in wells of a 96-well plate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The plant is highly rich in electron donating phytochemical compounds such as flavonoids, polyphenols, diterpenes and polysaccharides (Labulo et al, 2016). It is also reported that D. microcarpum has strong antioxidant capacity to scavenge free radicals such as intracellular ROS of cancer cells (Adebayo et al, 2019;Lamien-Meda et al, 2008;Rouamba et al, 2017). In this study, we synthesized silver nanoparticles using the extract of Detarium microcarpumleaves and the cytotoxic effects of the synthesized nanoparticles (dAgNPs) on pancreatic (PANC-1) and cervical (HeLa) cancer cells were evaluated for the first time.…”
Section: Inhibitory Effect Of Eco-friendly Naturally Synthesized Silvmentioning
confidence: 99%
“…Récemment, l'effet inhibiteur vis-à-vis des cellules cancéreueses MCF7 d'extrait méthanolique d'écorces de tige de G. senegalensis a été déterminé à l'aide du test de viabilité cellulaire Presto Blue. Il avait un effet antiprolifératif avec une CI 50 de 141 μg/mL et en outre, il présentait une action antimétastatique et induisait une apoptose (CI 50 de 29,8%) et un arrêt du cycle cellulaire dans les cellules MCF7 (Adebayo et al, 2019).…”
Section: Activité Cytotoxiqueunclassified